Peran Guru Pendidikan Agama Islam dalam Upaya Pembentukan Karakter Disiplin dan Tanggung Jawab Siswa di SMP Islam Jabal Hikmah: The Role of Pai Teachers in Efforts to Form Disciplinary Character and Student Responsibility at Jabal Hikmah Islamic Middle School - Zakaki (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
Education has a very important role for humans, both formal and non-formal, to develop basic abilities, both physical and spiritual, which can be developed as optimally as possible, so that humans can carry out their duties in life in the world. The aim of this research is to find out: what is the role of PAI teachers in efforts to build discipline character, responsibility, and supporting and inhibiting factors in the school. This research is a qualitative descriptive study. The research subjects were school principals, head of student affairs and students. Data collection was carried out by observation, interviews and documentation studies. The results of the research show that PAI teachers in their efforts to develop disciplined and responsible character demonstrate their roles, namely: the role of educator, the role of model and role model, and the role of motivator. In this effort to build character, there are supporting and inhibiting factors in its implementation. Supporting factors come from teachers, parents, the environment. Then the inhibiting factor comes from peers.